General practice patients treated for substance use problems: a cross-national observational study in Belgium - Nicole Boffin; Jerome Antoine; Sarah Moreels; Simeon Wanyama; Karin De Ridder; Lieve Peremans; Marc Vanmeerbeek; Viviane Van Casteren (BMC, 2016)
Abstract Background General Practitioners (GPs) are well placed to care for patients with (chronic) substance use problems. This pilot was carried out to study the feasibility and usefulness of a continuous surveillance of substance use problems among general practice patients. The objectives were (i) to describe variables with missing values exceeding 1% and whether patients were reported without substance-related problems; (ii) the profile and the magnitude of the patient population that is treated for substance use problems. Methods Observational study by the Belgian Network of Sentinel General Practices (SGP) in 2013. Baseline (at the first encounter) and 7-month follow-up data were reported of all patients treated for substance use problems. Two main measurements were type of substance use and patient status at follow-up. Multiple logistic regression analysis was used to examine patient status at follow-up. Results Of 479 patients, 47.2% had problems with alcohol alone, 20.3% with prescription drugs, 16.7% with illicit drugs other than heroin or methadone and 15.9% with heroin or methadone. Problems with alcohol alone were more prevalent in Flanders (53.0%; 95% confidence interval (CI) 46.8-59.1%) than in Wallonia-Brussels (39.8%; 95% CI 33.1-46.8%), while problems with heroin or methadone were more prevalent in Wallonia-Brussels (27.0%; 95% CI 21.1-33.5%) than in Flanders (7.1%; 95% CI 4.3-10.9%). At follow-up, 32.8% of the patients had dropped out, 29.0% had discontinued GP treatment and 38.2% had continued GP treatment. Overall, 32.4% of 479 patients had continued GP treatment for substance use problems during the study period. In Wallonia-Brussels, this proportion was higher (42.7%; 95% CI 35.9-49.6%) than in Flanders (24.3%; 95% CI 19.2-29.8%). Conclusions A continuous surveillance of the general practice population treated for substance use problems seems to be feasible and useful. The latter is suggested by the specific profile and the relative magnitude of the population. Inter-regional health system differences should be taken into account to estimate the epidemiology of substance use problems among general practice patients.